Odpowiedzi

2010-02-14T15:39:32+01:00
6(x+y)=10y
y-x=0,5

6x + 6y = 10y
y= 0,5 +x

6x = 4y
y = 0,5 +x

6x = 4(0,5 +x)
y = 0,5 +x

6x = 2 +4x
y = 0,5 + x

2x = 2 | :2
y = 0,5 +x

x = 1
y = 1,5
2010-02-14T15:39:43+01:00
6x+6y=10y
-x+y=0,5 /x6

6x-4y=0
-6x+6y=3

2y=3
y=1,5

y-x=0,5

1,5-x=0,5
x=1
  • hevi
  • Początkujący
2010-02-14T15:46:28+01:00
6(x+y)=10y
y-x=0,5

6x+6y-10y=0
y-x=0,5

6x-4y=0
y-x=0,5/*4

6x-4y=0
4y-4x=2
+_______________

6x-4y+4y-4x=2
2x=2/:(2)

x=1
y-x=0,5

x=1
y=0,5+1

x=1
y=1,5